(untitled) (Research, Society and Development, 2025)
The present study sought to analyze the literature and characterize the research instruments that address stress, depression and anxiety in university students. Explicit and systematic search methods were applied, based on the Cochranec Collaboration. To select the descriptors, we consulted the structured and trilingual vocabulary, of writers in Health Sciences (DeCS), Latin American and Caribbean Center for Information and Health Sciences (BIREME) and the Medical Subject Heandings (MeSH). The search for studies was carried out in databases that present high publications on the subject, namely: Directory of Open Access Journals (DOAJ), Directory of Open Access Scholarly Resources (ROAD) and Academic Search Premier, using the following descriptors as a search strategy and Boolean operators: “university student OR university study” AND “mental health OR mental health”. Database searches resulted in 422 studies, but only 15 met the inclusion criteria. In the 15 studies reviewed, 13 research instruments were found and their data were organized according to: a) general characterization of the studies and b) general characterization of the instruments. The studies analyzed revealed the absence of research instruments aimed exclusively at the university population, demonstrating the need to adapt and validate existing instruments to be used with students at this stage of life. This systematic review of the literature suggests the incorporation of cultural and specific elements present in the context of university students in order to ensure a better understanding of the challenges faced by this public.